PELATIHAN PEMBUATAN ES MINUMAN BUNGA TELANG (CLITORIA TERNATEA) OLEH IBU PKK DESA MALIKU BARU SEBAGAI INOVASI UMKM DAN STRATEGI PEMASARAN - Ade Novalia; Dian Indriani; Diva Luthfi Anggara Putra; Elae Saputri; Elmawati, Elmawati; Kesya Ivena Br Ginting; Kristin Natalia; Lalu Sandu Baya; Martitus Wiranata; Ociyo Naibaho; Ridwan Bangun; Riri Florentia; Stefanny M. Simalango; Yolanika, Yolanika; Rahmat Tajudinnur; Agtri Wulandari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The butterfly pea (Clitoria ternatea) contains anthocyanins and flavonoids with antioxidant, antihypertensive, and antidiabetic properties. However, in Maliku Baru Village its use remains limited to ornamental purposes, resulting in low economic value. This community engagement program aimed to enhance the skills of the local women’s group (PKK) in processing butterfly pea into healthy, marketable beverages, while also introducing basic digital marketing strategies to strengthen village-based micro, small, and medium enterprises (MSMEs). The program employed a Participatory Action Research (PAR) approach, involving problem identification, production training, hygienic packaging, and digital promotion. Fifteen participants took part in the training, with outcomes evaluated through pre- and post-tests. The results demonstrated significant improvement in both production and marketing skills, particularly in digital marketing, which increased by nearly 90%. Participants were able to produce butterfly pea beverages independently and began promoting their products through official village social media platforms. This program proved effective in improving community capacity in utilizing local resources and is expected to continue with further assistance in business management, product packaging, and food safety certification to enhance product competitiveness.